PENGARUH LEADERSHIP STYLE TERHADAP HOTEL EMPLOYEE COMMITMENT TO SERVICE QUALITY - Herry E. Asmansyah (Jurnal Manajemen dan Pemasaran Jasa, 2009)
The conceptual framework consists of the following constructs: .Management Commitment to Service Quality, Directive Leadership, Participative Leadership, Empowering Leadership, Role Clarity, Shared Values, Employees Commitment to Service Quality, and Job Satisfaction. Moreover, 3 hypotheses were developed and tested. Instrument test of validity and reliabilty used to test the validity of the measures, while structural equation model was used in hypotheses testing. Data were collected from 101 employee who had worked at Aryaduta Hotel at Pekanbaru.Keywords: Management Commitment to Service Quality, Leadership Style, and Frontline Employee Responses.